2016
DOI: 10.1080/17290376.2016.1242434
|View full text |Cite
|
Sign up to set email alerts
|

Gendered differences in AIDS and AIDS-related cause of death among youth with secondary education in South Africa, 2009–2011

Abstract: Background: The prevalence of human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) is higher among females than males in Sub-Saharan Africa. Education is associated with better health outcomes. For this and other reasons, African countries have made a concerted effort to increase youth education rates. However, in South Africa males have lower secondary education rates than females, yet females have a higher prevalence of HIV/AIDS. This study examines if a gender disparity exists in AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Females are at risk of getting infected by the disease in situations where they are poor and need financial assistance for survival and therefore will fall prey. De Wet [25] investigated the gender difference in AIDS among secondary school youth in South Africa and showed that the prevalence of HIV is higher among females than males; she further demonstrated that AIDS mortality is lower for females than males in secondary school, although it is still high for females.…”
Section: Discussionmentioning
confidence: 99%
“…Females are at risk of getting infected by the disease in situations where they are poor and need financial assistance for survival and therefore will fall prey. De Wet [25] investigated the gender difference in AIDS among secondary school youth in South Africa and showed that the prevalence of HIV is higher among females than males; she further demonstrated that AIDS mortality is lower for females than males in secondary school, although it is still high for females.…”
Section: Discussionmentioning
confidence: 99%
“…Culturally entrenched gender norms determine agency regarding the negotiation of safe sexual practices, and this is reflected in the consistent finding of lower condom use among young women compared to their male peers (De Wet, 2016;HSRC, 2018;Jukes, Simmons, & Bundy, 2008). Deliberations that are restricted to merely enhancing female agency in sexual relationships obfuscate the wider cultural roles that young males often adopt when engaging in such behavior.…”
Section: Cultural Factors That Influence Hiv Prevention and Treatmentmentioning
confidence: 99%
“…Gender inequities provide one explanation for the conspicuous sex differences in the dispersal of HIV across South Africa with 62% of seropositive cases attributed to women and new infections three times higher among females under 25 years compared with males of the same age group 2 . As a result, HIV symptoms occur 5–7 years earlier for seropositive women compared with men and adolescent girls die of HIV infection at disproportionate rates 3,4 . Structural gender inequality leaves a unique imprint on South African women’s lives, curbing their educational and economic opportunities and fostering dependency on men even at the cost of their health 5 .…”
Section: Introductionmentioning
confidence: 99%